Pengaruh Komunikasi Pemasaran Berbasis Etika Dalam Menciptakan Nilai Pelanggan Dan Dampaknya Terhadap Loyalitas Pelanggan Susu Formula Bayi Di Indonesia - Nurudin, Agus (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to analyze the influence of ethics-based integrated marketing communication on customer value creation and its impact on customer loyalty in the infant formula industry in Indonesia. This industry operates under strict ethical codes set by the World Health Organization (WHO) and reinforced by Indonesian Ministry of Health Decrees No. 237/IV/Menkes/1997 and No. 450/IV/Menkes/2004, prioritizing breastfeeding. However, weak enforcement of ethical codes and the reciprocal relationship between healthcare professionals and companies create potential ethical challenges. The research was conducted in three major cities—Jakarta, Surabaya, and Makassar—using healthcare professionals such as doctors, pediatricians, midwives, and nurses as units of analysis. The study employed interviews and surveys with random and stratified random sampling methods. Primary data were analyzed using Structural Equation Modeling (SEM) via Lisrel 8.70. Results show that ethics-based integrated marketing communication has a positive and significant effect on customer value (coefficient 0.912; t-value 10.29 ? 1.96) but does not directly affect customer loyalty (coefficient 0.009; t-value 0.041 ? 1.96). Indirectly, it significantly influences loyalty through customer value (coefficient 0.849). Customer value has a positive and significant direct effect on loyalty (coefficient 0.931; t-value 4.075 ? 1.96), indicating that customer value acts as a key mediator in enhancing healthcare professionals’ loyalty toward infant formula products.